Modelling and demonstration of electromagnetically assisted stamping system using an interactive mapping method. (August 2018) - Li, She; Cui, Xiangyang; Li, Guangyao
Highlights: A novel modelling for electromagnetically assisted stamping (EMAS) process is proposed. Address the key theoretical problem in simulation of EMAS process. Build a bridge between conventional stamping and electromagnetic forming. Applied in EMAS process with complex structure of industrial applications is feasible and promising. Abstract: Electromagnetically assisted stamping (EMAS) process is an innovative hybrid sheet metal forming technique that combines electromagnetic forming (EMF) into quasi-static conventional stamping. This paper presents a numerical modelling based on a novel triangular prism solid and shell interactive mapping element for EMAS process. In the present work, the triangular prism solid and shell interactive mapping element builds a bridge between conventional stamping and electromagnetic forming (EMF) process, in which shell element is employed in conventional stamping process. A linear six-node prism element is developed for transient eddy current analysis in electromagnetic field of EMF process. An interactive mapping rule is established to transfer information between different type elements, accordingly. That is to say, one can take full advantages of shell element solving stamping problems with contact condition in EMAS process. Electromagnetically assisted stamping example is used for validation of the present modelling. The proposed numerical modelling can successfully simulate the combined quasi-static-dynamic process, and the numerical results predict the experimental ones. The present modelling produces potential for further study in EMAS process. Graphical abstract: Image, graphical abstract Electromagnetically assisted stamping (EMAS), which consists of a conventional stamping process and an electromagnetic forming (EMF) process, combines the advantages of high-speed EMF on forming aluminum and magnesium alloys into the conventional stamping process.